Chlorpyrifos residue levels on field crops (rice, maize and soybean) in China and their dietary risks to consumers. (May 2015) - Li, Rui; He, Liang; Wei, Wei; Hao, Lili; Ji, Xiaofeng; Zhou, Yu; Wang, Qiang
Abstract: In this study, chlorpyrifos residue levels in field crops of rice, maize and soybean were investigated according to the "Guideline on Pesticide Residue Trials" of China. On the basis of the residual results, human dietary risks were further evaluated. Chlorpyrifos residues of harvest grains were firstly prepared by QuEChERS method and analyzed using Gas Chromatography Tandem Mass Spectrometry (GC–MS/MS). Dietary risks were assessed by a deterministic approach. The median residues in field trials of rice, maize and soybean were 0.617, 0.0227 and 0.0136 mg kg −1, respectively. The highest residues in field trials of rice, maize and soybean were 3.23, 0.114 and 0.102 mg kg −1, respectively. Chronic intake assessment indicated that only 39.0% of acceptable daily intake (ADI, 0–0.01 mg kg bw −1  day −1 ) was consumed through rice, maize and soybean. The acute hazard indexes (aHI) of adults was 26.1% of acute reference dose (ARfD, 0–0.1 mg kg bw −1 ) and aHI of children was 63.5% of ARfD in dietary exposure assessment through rice, maize and soybean consumption. Single pathway risk assessment indicated that chlorpyrifos application on field crops in manner of the good agricultural practices didn't pose public health risks. Highlights: Chlorpyrifos safety evaluation for crops of rice, maize and soybean in China. Chlorpyrifos theoretical exposure for human diet in China. The supervised field trials for residue behaviors investigation.